Markers of intravascular coagulation and fibrinolysis in preeclampsia: association with intrauterine growth retardation - Rune Schjetlein; Guttorm Haugen; Finn Wisløff (Acta Obstetricia et Gynecologica Scandinavica)
Background. Alterations in blood coagulation and fibrinolysis are believed to play an important role in the pathogenesis of preeclampsia. Hypercoagulability may be associated with features seen in preeclampsia, such as fibrin deposition in various organs, consumptive thrombocytopenia, and placental hypoperfusion, insufficiency and infarction. Methods. In this cohort study, we compared the plasma levels of markers of blood coagulation and fibrinolysis in preeclamptic women to normotensive, pregnant controls. We also studied the association between these markers and intrauterine growth retardation (IUGR). Results. In both mild and severe preeclampsia, the mean plasma concentrations of thrombin‐antithrombin III complex (TAT) and plasminogen activator inhibitor type 1 (PAI‐1) activity were significantly increased, while fibrinogen, antithrombin III (ATIII) and plasminogen activator inhibitor type‐2 (PAI‐2) antigen levels were significantly reduced compared to controls. Plasma D‐dimer concentration was significantly higher in severe, but not in mild preeclampsia compared to the controls. The plasma level of fibrin monomer was similar in patients and controls. Patients with preeclampsia delivering growth retarded infants had significantly lower PAI‐1 activity and PAI‐2 antigen concentrations in plasma than the remaining preeclamptic women. Conclusions. We found evidence of increased intravascular coagulation and fibrin turnover in preeclampsia. Low PAI‐2 antigen plasma levels were associated with severe preeclampsia and IUGR.